(untitled) (International Journal of Physiotherapy, 2016)
Background: To investigate the effectiveness of four weeks sports specific balance training program to improve balance, thus reducing the risk of ankle sprain among Sultan Idris Education University basketball players. Method: There were 20 males basketball players (aged 19-24 years) volunteered in this study. After screening process, there were14 male players met the inclusion criteria. They were randomized into two groups i.e experimental group (EG: n=7) and control group (CG: n=7). The EG undergone the four weeks sports specific balance training program three times per week while the CG followed their normal standard basketball training program. Balance Error Scoring System (BESS) was used to assess static balance while Star Excursion Balance Test (SEBT) is utilized to examine the dynamic balance. Pretest and posttest of balance measures were recorded using BESS and SEBT for both EG and CG. The data were analyzed using independent sample t-test (p=0.05). Results: The study findings indicated that there were significant differences between EG and CG for the static balance on firm surface (t=-4.642, p=0.001) and on foam surface (t=-8.590, P=0.000) as well as dynamic balance on left leg stance (t=2.350, P=0.037) and on right leg stance (t=3.145, P=0.008). Conclusion: The study findings indicated that the four weeks sports specific balance training program could improve balance ability in male basketball players, thus may reducing the risk of ankle sprain.